Tipology of Value Orientations of Ukrainians (Based on the Data of European Social Survey) - Uliana Leshenok (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Соціологічні дослідження сучасного суспільства: методологія, теорія, методи, 2019)
The article is devoted to the analysis of value orientations of Ukrainians based on the data of six waves of the European Social Survey (2004-2012). The aim is to identify the structure of Ukrainian society on the basis of the value orientations of respondents, obtained by the public opinion polling. The dynamics of this structure is also analyzed during 2004-2012. The concept of "value" in this article is defined within Schwartz's theory as desirable goals that go beyond specific situations, differ in importance from each other and are guiding principles in human life. The analysis uses the ten Schwarz's values, which are grouped into four value sectors, which are named «Conservation», «Self-Enhancement», «Self-Transcendence» and «Openness to Change». To identify the structure respondents were divided into three clusters, depending on the expressiveness of value orientations in each sector. The clustering was carried out using the k-means method, while the cluster centers were wrote based on the theoretical conception: the first cluster includes respondents with the most expressed values of «Self-Enhancement» and «Openness to Change», the second one – respondents with the most expressed values of «Self-Transcendence» and «Conservation», the third one – respondents who are closes to average values of all four sectors. The resulting cluster structure was identified in each of the six waves of the European Social Survey. At the same time clusters are differ in a number of socio-demographic indicators, as well as in some social orientations. The third cluster is biggest in the each wave of the survey. It means that the group of respondent who doesn’t have strongly expressed values of any of four sectors is the biggest. It can be explained by the phenomenon of ambivalence of the individual that means combination of views, thoughts, feelings, orientations that are mutually exclusive. It was also found that the trend of increasing the expressiveness of the values of «Self-Enhancement» and «Openness to Change», which manifests itself in the array as a whole, is also observed within the first and third clusters, but the value orientations of the second cluster remain relatively stable.